2010
DOI: 10.2486/indhealth.ms962
|View full text |Cite
|
Sign up to set email alerts
|

Job Strain among Rubber-Glove-Factory Workers in Central Thailand

Abstract: Job strain has become a major concern because of its potential impacts on worker well-being and performance. This cross-sectional study aimed to assess the prevalence of, and examine factors associated with, job strain among workers in a rubber-glove factory, in a central province of Thailand. A total of 200 workers aged 18-55 yr, who had worked at the factory for at least 6 months, completed the Job Content Questionnaire (JCQ) (Thai Version). Two of 5 scales in the JCQ were used to measure job strain, i.e.; j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
3
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 26 publications
3
15
3
5
Order By: Relevance
“…In a similar study, carried out by Sein et al, using Job Content Questionnaire, in April 2009, on 200 rubber glove factory employees in central Thailand revealed; prevalence of job stress was 27.5% and Low supervisor social support and high job insecurity were found to be associated factors. 8,16 The experience of occupational stress due to pressure from overload, personal responsibilities and managerial role, may be due to their position in the industry and have to work up to the expectation of their seniors. It was well expected by managers and supervisors as they are to show their ability to reach higher position in the organization and consequently experience more work stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a similar study, carried out by Sein et al, using Job Content Questionnaire, in April 2009, on 200 rubber glove factory employees in central Thailand revealed; prevalence of job stress was 27.5% and Low supervisor social support and high job insecurity were found to be associated factors. 8,16 The experience of occupational stress due to pressure from overload, personal responsibilities and managerial role, may be due to their position in the industry and have to work up to the expectation of their seniors. It was well expected by managers and supervisors as they are to show their ability to reach higher position in the organization and consequently experience more work stress.…”
Section: Discussionmentioning
confidence: 99%
“…equipment's used), work-systems (E.g., work-load or work pace, work schedule or working hours). 5,8 Reddy and Ramamurthy concluded that stress was found to be considerably influenced by age-related factors among 200 male executives. 9 Sharma reported a finding from a study by the Defence Institute of Psychological Research (DIPR) which revealed that increase in the occupational factors such as years of job experience and job hierarchy increased the levels of stress among officers, junior commissioned officers (JCO) and jawans.…”
Section: Introductionmentioning
confidence: 99%
“…No mundo universitário observou-se o estresse devido à redução dos financiamentos do governo e no aumento das demandas sobre as ações intelectuais (WINE-FIELD et al, 2003;LIU, SPECTOR;SHI, 2008;CATANO et al, 2010). No ambiente industrial, foi por meio das metas de produção a serem conquistadas (MOHAN et al, 2008;SEIN et al, 2010).…”
Section: Resultsunclassified
“…Literatura navaja poleg demografskih in osebnostnih značilnosti, kot so visoka izraženost nevroticizma in psihoticizma ter nizka ekstravertnost, ki neodvisno prispevajo k razvoju izgorelosti zaposlenih (6), tudi nekatere psihosocialne stresorje na delovnem mestu, kot so velike zahteve dela, pomanjkanje povratnih informacij o delu, majhen vpliv na odločitve, nestrinjanje zaposlenega z vrednotami na delovnem mestu in pomanjkanje socialne podpore, ki lahko predstavljajo velika tveganja za razvoj izgorelosti v okviru različnih poklicnih profilov (3,7,8). Različne študije med poklice z visokim tveganjem za razvoj SPD poleg zdravstvenih delavcev (9,10) in učiteljev (10) uvrščajo tudi menedžerje (11,12) ter administrativne (12) in proizvodne delavce (13). V zdravstveni dejavnosti se povečana stopnja SPD pripisuje različnim izvorom stresa: preobremenjenosti z delom, nestalnim delovnim urnikom, čustveni naravi dela, odnosu z delovnim mentorjem/nadrejenim, nejasnosti in konfliktnosti vlog, organizacijski klimi (14), medtem ko pri menedžerjih prevladujejo stresorji, kot so: velika odgovornost za poslovne izide organizacije, dolg delovni čas, medosebni odnosi med sodelavci in vodstvom (15,16).…”
Section: Uvodunclassified
“…Podobno ugotavljajo primerljive raziskave, ki poročajo o zdravstvenih delavcih in delavcih v proizvodnji kot ranljivejših poklicnih skupinah za razvoj SPD (10,13). V nasprotju z nekaterimi izsledki o precej izraženem in pogostem doživljanju SPD pri vodstvenih delavcih (11,12,15,16) so udeleženci na vodstvenih položajih v naši raziskavi poročali o primerljivi stopnji poklicnega stresa glede na druge poklicne skupine.…”
Section: Razpravaunclassified